Identifikasi Dimensi Utama, Tren Penelitian, dan Peluang Pengembangan Sustainability Design Melalui Pendekatan Systematic Literature Review - Yati Bt samsuddin; Andry Priyadharmadi Purnama (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to identify the main dimensions, research trends, as well as Research gaps and development opportunities in sustainability design through a systematic literature review (SLR) approach. The review process was conducted systematically by following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, which includes the stages of identification, screening, eligibility, and inclusion. Data were collected from the Scopus database within the publication range of 2016–2026 using relevant keywords, resulting in four articles that met the inclusion criteria for analysis. The findings reveal that sustainability design is a multidimensional concept consisting of four main dimensions: environment-based systemic approach, user experience, human well-being, and technology integration in design education. In addition, the study identifies a shift in research trends from conceptual approaches toward empirical and integrative methods that combine quantitative and qualitative techniques. The study also highlights significant Research gaps, particularly the lack of integration among these dimensions within a comprehensive conceptual framework, as well as methodological limitations in previous studies. In conclusion, sustainability design needs to be developed through a more holistic and integrative approach to address the complexity of sustainability challenges.